A metasurface‐based broadband quasi nondispersive cross polarization converter for far infrared region. Issue 10 (1st July 2019) - Nilotpal,; Nama, Lavesh; Bhattacharyya, Somak; Chakrabarti, Parthasarathi
Abstract: A broadband nondispersive cross polarization converter (CPC) structure using metasurface for far infrared region has been proposed in this article. The structure is transmittive in nature, which converts a linearly polarized incident wave to its mutually orthogonal linearly polarized wave over a band of frequency ranging from 10.25 to 22.7 THz maintaining a high polarization conversion ratio (PCR) of more than 0.95. The fractional bandwidth of 75.6% corresponding to the center frequency of PCR bandwidth having more than 0.9 PCR value has been realized. The structure is also studied for oblique incidences where it shows wide band polarization conversion up to 45° for both TE and TM polarized oblique incident waves. The electric field distributions at the top and bottom surfaces of the structure close to the center frequency of polarization conversion bandwidth indicate the orthogonal rotation of incident linearly polarized wave at the frequency of interest. For the given set of media interface a separate study on polarization conversion through Brewster angle concept has been carried out simultaneously. The structure exhibits high PCR by maintaining the compactness in thickness (~ λ /5) as well as periodicity (~ λ /3) compared to the existing reported ones.